Mechanochemical synthesis of ceramic powders with perovskite structure - Stojanovic, B. D. (Elsevier B.V., 2003)
The mechanical activation is one of the most effective method for obtaining highly disperse system due to mechanical action stress fields form in solids during milling procedure. This effect results in changes of free energy, leading to release of heat, formation of a new surface, formation of different crystal lattice defects and initiation of solid-state chemical reaction. The accumulated deformation energy determines irreversible changes of crystal structure and consequently microstructure resulting in the change of their properties. Mechanochemical processing route has been developed recently for the production of intermetallic and alloy compounds. The intrinsic advantage of this process is that the solid-state reaction is activated due to mechanical energy instead of the temperature. It was shown that the chemical reactivity of starting materials could be improved significantly after mechanochemical activation and, subsequently, the calcination temperature was reduced. Besides, it was apparent that the mechanochemical treatment could enhance the reactivity of constituent oxides; however, the sintering process could not be avoided to develop the desired ceramics. A novel mechanochemical technique for synthesis of fine-grained perovskite structured powders has shown that it is possible to form perovskite at room temperature. The effect of milling on the formation of perovskite structure of barium titanate (BT), lead titanate (PT), PZT, PZN, magnesium niobate (PMN) and LM ceramic materials was analyzed. The dielectric properties of sintered ceramics are comparable with those prepared by other methods in the literature. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: mechanochemical synthesis; ceramic powders; perovskite structure